“How is my body going to cope with it? How should I go on with my life?” Reflections on occupational future: interview study with cardiac rehabilitation patients with vocational reintegration risk - Wolff, Lara Luisa; Luizink-Dogan, Machteld; Holmberg, Christine; Völler, Heinz; Salzwedel, Annett (Die Rehabilitation, 2025)
Patients in cardiac rehabilitation (CR) with subjectively impaired occupational prognosis are at risk of not returning to work (RTW) in the medium term. This study aimed to explore, describe and summarise the aspects relevant in CR patients’ reflections on their occupational future.A qualitative study was conducted in CR in 2021/22; 25 patients (median age 52 years; 9 women, 16 men; working in different physically demanding occupations; 20 with risk of non-RTW and 5 without by the Würzburger Screening) were interviewed and asked to reflect on their occupational future.About 6–8 months post-CR, 8 patients were re-interviewed to check the relevance of the factors identified during CR. All interviews were recorded, transcribed and thematically analysed.Aspects relevant for the reflection on subjectively perceived occupational future could be summarised into internal factors: personal aspects, health perception, heart-focused anxiety, and external factors: social circle and adjustments in work conditions. Two further themes were time-related: prior health/illness-related experiences and intended work and lifestyle changes. Especially participants with a risk of non-RTW experienced heart-focused anxiety, contemplated previous health/illness experiences and expressed a desire to RTW in the distant future, although they had no clear plan of action. Greater emphasis was placed on prioritising health and taking time for RTW, and participants often felt supported in this by their social environment. Themes were overlapping between participants with and without risk of non-RTW, yet different in relevance and detail.Overall, patients at different risk of non-RTW reflecting on their subjective perception of occupational future show similarities regarding relevant aspects and themes. However, especially patients at risk of non-RTW reflected on perceived heart-focused anxiety and the lack of concrete RTW plans for their occupational future. These aspects should be considered in individual, holistic and goal-oriented approaches to support patients on their RTW journey.
Keywords: cardiac rehabilitation; occupational prognosis; return to work